Array tomography: characterizing FAC-sorted populations of zebrafish immune cells by their 3D ultrastructure - Wacker, Irene; Chockley, Peter; Bartels, Carolin; Spomer, Waldemar; Hofmann, Andreas; Gengenbach, Ulrich; Singh, Sachin; Thaler, Marlene; Grabher, Clemens; Schröder, Rasmus R. (Journal of microscopy, 2015)
For 3D reconstructions of whole immune cells from zebrafish, isolated from adult animals by FAC-sorting we employed array tomography on hundreds of serial sections deposited on silicon wafers. Image stacks were either recorded manually or automatically with the newly released ZEISS Atlas 5 Array Tomography platform on a Zeiss FEGSEM. To characterize different populations of immune cells, organelle inventories were created by segmenting individual cells. In addition, arrays were used for quantification of cell populations with respect to the various cell types they contained. The detection of immunological synapses in cocultures of cell populations from thymus or WKM with cancer cells helped to identify the cytotoxic nature of these cells. Our results demonstrate the practicality and benefit of AT for high-throughput ultrastructural imaging of substantial volumes.